ROS programming : building powerful robots : design, build and simulate complex robots using the Robot Operating System /: building powerful robots : design, build and simulate complex robots using the Robot Operating System. (2018) - Mahtani, Anil; Sanchez, Luis; Fernández, Enrique (Fernández Perdomo); Martinez, Aaron; Joseph, Lentin
No abstract available